2019
DOI: 10.1186/s12913-019-4132-z
|View full text |Cite
|
Sign up to set email alerts
|

Social network analysis of rural medical networks after medical school immersion in a rural clinical school

Abstract: Background The impact of new medical graduates on the social dimensions of the rural medical workforce is yet to be examined. Social Network Analysis (SNA) is able to visualize and measure these dimensions. We apply this method to examine the workforce characteristics of graduates from a representative Australian Rural Clinical School. Methods Participants were medical graduates of the Rural Clinical School of Western Australia (RCSWA) from the 2001–2014 cohorts, identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Other studies identified that graduates who had participated in a rural clinical school (RCS) during their training, were more likely to undertake rural and remote work in years following graduation [15,30,31,36,38,42,47,48,52,57,[59][60][61]. However, it was identified that this rural work was not always sustained [42] and that graduates had limited prior contact with the rural areas in which they were working [50]. Other models of rural training included a partnership between a university and a health service to deliver a rural training program, with research finding that graduates who had participated in the program were more likely to remain local for an internship, as well as following an internship [44].…”
Section: Medicinementioning
confidence: 99%
“…Other studies identified that graduates who had participated in a rural clinical school (RCS) during their training, were more likely to undertake rural and remote work in years following graduation [15,30,31,36,38,42,47,48,52,57,[59][60][61]. However, it was identified that this rural work was not always sustained [42] and that graduates had limited prior contact with the rural areas in which they were working [50]. Other models of rural training included a partnership between a university and a health service to deliver a rural training program, with research finding that graduates who had participated in the program were more likely to remain local for an internship, as well as following an internship [44].…”
Section: Medicinementioning
confidence: 99%
“…For example, the Rural Clinical School of Western Australia distributes rural medical workforce in a clearly geographically patterned way, with Broome acting as a bridge to the remote north of Australia. 40 In Victoria, those selected from a specific region and having greater than one year of rural training in that region had a 17.4 times increased chance of working in that same rural region compared with urban background students who had completed fewer than 12 weeks of training in the region. 25 In rural communities, students make an authentic contribution to the clinical care of patients.…”
Section: Immerse Students In a Rural Placementioning
confidence: 99%
“…This argument is suggested by social network analysis of RCSWA graduate work choices, which showed a strong social patterning of graduate rural work choices. Choices were not ordered by the usual factors of location to capital city, size of town, affluence of town or availability of specialist resources, 21 but appeared rather to relate to social aspects of the work location 22 …”
Section: Introductionmentioning
confidence: 99%